Drinking, Alcohol Use Disorder, and Treatment Access and Utilization among U.S. Racial/Ethnic Groups - Vaeth, Patrice A.C. (Alcohol Clin Exp Res, 2016)
Data from approximately 140 articles and reports published since 2000 on drinking, alcohol use disorder (AUD), correlates of drinking and AUD, and treatment needs, access and utilization were critically examined and summarized. Epidemiological evidence demonstrates alcohol-related disparities across U.S. racial/ethnic groups. American Indians/Alaska Natives generally drink more and are disproportionately affected by alcohol problems, having some of the highest rates for AUD. In contrast, Asian Americans are less affected. Differences across Whites, Blacks and Hispanics are more nuanced. The diversity in drinking and problem rates that is observed across groups also exists within groups, particularly among Hispanics, Asian Americans, and American Indians/Alaska Natives. Research findings also suggests that acculturation to the U.S. and nativity affect drinking. Recent studies on ethnic drinking cultures uncover the possible influence that native countries’ cultural norms around consumption still have on immigrants’ alcohol use. The reasons for racial/ethnic disparities in drinking and AUD are complex and are associated with historically-rooted patterns of racial discrimination and persistent socioeconomic disadvantage. This disadvantage is present at both individual and environmental levels. Finally, these data indicate that admission to alcohol treatment is also complex and is dependent on the presence and severity of alcohol problems but also on a variety of other factors. These include individuals’ sociodemographic characteristics, the availability of appropriate services, factors that may trigger coercion into treatment by family, friends, employers and the legal system, and the overall organization of the treatment system. More research is needed to understand facilitators and barriers to treatment to improve access to services and support. Additional directions for future research are discussed.